High frequency performance analysis of professional soccer goalkeepers: a pilot study - Padulo, J.; Haddad, M.; Ardigò, L. P.; Chamari, K.; Pizzolato, F (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: High-speed video analysis was performed during ten official-matches, to assess the performance of ten goalkeepers (GK) from Italian third/fourth divisions (C-D).